8.1k views
5 votes
Find the sum.
2(-5y+6)+(2y-8)

1 Answer

0 votes

Answer: I am just hoping that this is the correct answer

Explanation:

2(-6 + -5y) + (2y + -8) = 0

(-6 * 2 + -5y * 2) + (2y + -8) = 0

(-12 + -10y) + (2y + -8) = 0

Reorder the terms:

-12 + -10y + (-8 + 2y) = 0

Remove parenthesis around (-8 + 2y)

-12 + -10y + -8 + 2y = 0

Reorder the terms:

-12 + -8 + -10y + 2y = 0

Combine like terms: -12 + -8 = -20

-20 + -10y + 2y = 0

Combine like terms: -10y + 2y = -8y

-20 + -8y = 0

Solving

-20 + -8y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '20' to each side of the equation.

-20 + 20 + -8y = 0 + 20

Combine like terms: -20 + 20 = 0

0 + -8y = 0 + 20

-8y = 0 + 20

Combine like terms: 0 + 20 = 20

-8y = 20

Divide each side by '-8'.

y = -2.5

Simplifying

y = -2.5

User Sudoz
by
5.2k points